Dynamic Analysis of Wind Turbine Towers on Flexible Foundations - S. Adhikari; S. Bhattacharya (Shock and Vibration)
Offshore wind turbines are considered as an essential part to develop sustainable, alternative energy sources. The structures themselves are both slender and highly flexible, with a subsea foundation typically consisting of a single large diameter monopile. They are subject to intense wind and wave loadings, with the result that significant movement of both the exposed structure and the upper part of the monopile can occur. Although the structures are intended for design life of 25 to 30 years, very little is known about the long term behaviour of these structures. This paper characterizes the dynamic behaviour of these structures. A simplified approach has been proposed for the free vibration analysis of wind turbines taking the effect of foundation into account. The method is based on an Euler-Bernoulli beam-column with elastic end supports. The elastic end-supports are considered to model the flexible nature of the interaction of these systems with the foundation. A closed-form expression of the characteristic equation governing all the natural frequencies of the system has been derived. Theoretical developments are explained by practical numerical examples. Analytical as well as a new experimental approach has been proposed to determine the parameters for the foundation. Some design issues of wind turbine towers are discussed from the point of view of the foundation parameters.